To explore the therapeutic effect of Kangfuxiaomi shuan II on cervicitis in rats - Duan,Xiao-Mei (2021)
ABSTRACT Purpose: The rat cervicitis model was established with 20% phenol glue to explore the therapeutic effect of Kangfuxiaomi shuan II on rat cervicitis and its mechanism. Methods: After modeling, the rats were treated with Shuangzuotai suppository (37.84 mg/kg), Kangfuxiaoyan shuan (205.6 mg/kg) and Kangfuxiaomi shuan II (40, 80, 160 mg/kg). The histopathological changes and injury degree of cervix in rats were evaluated by vulvar inflammation score and organ index. The therapeutic effect of Kangfuxiaomi shuan II on cervicitis was evaluated by detecting the levels of copper-protein (CP), C-reactive protein (CRP), Rat interleukin 6 (IL-6), superoxide dismutase (SOD) and malondialdehyde (MDA) in serum and epidermal growth factor (EGF), cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) in cervical tissue. Results: Compared with the model group, the vulvar inflammation score and cervical index of rats in other groups decreased significantly (P<0.01). Kangfuxiaomi shuan II could significantly reduce the levels of CP, CRP, and MDA in serum of rats with cervicitis, and significantly increase the activity of SOD in serum of rats with cervicitis (P<0.01). The levels of EGF and iNOS in cervical tissue of rats also increased in different degrees, while the level of COX-2 decreased significantly (P<0.01), which significantly improved the pathological degree of vulvar inflammation in rats with cervicitis. Conclusions: Kangfuxiaomi shuan II has a certain therapeutic effect on cervicitis in rats, and its mechanism may be related to the regulation of inflammatory cytokine network and immunity.